Global House Price Fluctuations : Synchronization and Determinants - Hirata, Hideaki (IMF Working Papers; Working Paper, 2013)
We examine the properties of house price fluctuations across 18 advanced economies over the past 40 years. We ask two specific questions: First, how synchronized are housing cycles across these countries? Second, what are the main shocks driving movements in global house prices? To address these questions, we first estimate the global components in house prices and various macroeconomic and financial variables. We then evaluate the roles played by a variety of global shocks, including shocks to interest rates, monetary policy, productivity, credit, and uncertainty, in explaining house price fluctuations using a wide range of FAVAR models. We find that house prices are synchronized across countries, and the degree of synchronization has increased over time. Global interest rate shocks tend to have a significant negative effect on global house prices whereas global monetary policy shocks per se do not appear to have a sizeable impact. Interestingly, uncertainty shocks seem to be important in explaining fluctuations in global house prices.